Psikoedukasi tentang Stigma Gangguan Jiwa di Masyarakat - Zaini, Mad; Komarudin; Insyirrah, Pembayun Cikal; Syah, Alif Firman (STIKES Ngesti Waluyo, 2024)
The stigma of mental disorders is one of the factors that hinders the care of people with mental disorders, especially those treated at home. This research aims to determine the description of the stigma of people with mental disorders in Botolinggo Village, Bondowoso Regency. Botolinggo Village is one of the villages that has a mental health alert village program. The design in this research uses a quantitative descriptive approach, with a population of 16 respondents taken using purposive sampling. The instrument used in this research was the Community Attitudes Toward The Mentally Illness (CAMI) Questionnaire. Univariate data analysis uses mean, median, and standard deviation, while bivariate data analysis uses the Pearson correlation test. The results of the univariate analysis show that the stigma of mental disorders in Botolinggo Village, Bondowoso Regency, tends to be low, and they have a positive attitude toward mental health problems. Based on the stigma domain, the highest domain is the benevolence domain, which means that the Bottlinggo community has a good, sympathetic, and humanistic attitude towards people with mental disorders.